The Haven : A Novel - Fisher, Suzanne Woods (Grand Rapids, MI : Revell, 2012)
When Sadie Lapp discovers an abandoned baby on her doorstep, the rumors begin to fly in her peaceful Amish community.
Includes discussion questions.
Keywords: Amish -- Fiction; Love stories; Christian fiction